Dynamics of vasoconstriction and vasodilation potential on the background of experimental rhegmatogenous retinal detachment and its correction - I. V. Savytskyi; I. M. Levytskyi; G. V. Levytska; I. V. Miastkivska; I. A. Kuzmenko (Kazimierz Wielki University, 2016)
Purpose: investigation of vasoconstriction and vasodilation potential in rhegmatogenous retinal detachment pathogenesis and analysis of correction methods effectiveness. It's proven that endothelial dysfunction is an important link in the pathogenesis of experimental rhegmatogenous retinal detachment. Balance violation of the vasoconstrictor and vasodilator potential in the direction of vasoconstriction predominance mechanisms against the background of the studied pathology is established.On the background of experimental rhegmatogenous retinal detachment found increased endothelin-1 level by 16.1%, and S-nitrosothiols level decreased by 26.3% in the blood of the experimental animals. The most characteristic changes were detected at the 21st day (p